PENGARUH TINGKAT PENJUALAN ALBUM KEPADA VOLATILITAS HARGA SAHAM PERUSAHAAN S.M. ENTERTAINMENT Co.Ltd - Permatasari, Ghaisani Ayu; Supriyatna, Yayat; Purnamasari, Imas (Journal of Business Management Education (JBME), 2017)
Objective - The research  is done to investigate the influence of information employment in the form of sales album to volatility stock prices to companies S.M. .Entertainment co.ltd the period 2012-2015 .The study is done to reduce the risk to investors shareholders and company. Design/methodology/approach - This research  has type descriptive and verikatif, using techniques descriptive analysis and statistical analysis with the simple regression is on the application eviews as the tools, and those research is amount of sales album and volatility stock prices were based on quarter,totaly 16 quarter.Findings - The level of the sale of the movement of the album and volatility company shares having a pattern of similar and stock prices firm bc .Entertainment co.ltd 2012-2015 period showed if the companies have shares with a kind of elastic .Originality/value - The difference this research are the object of research, study time, measuring instruments, and research results. The theory in this research using journals and books as a support, so the theory used is the different theories and supporting this research. Keywords : Employment Information, Stock Price Volatility, Stock Price, Employment, Album Selling, Entertainmnet, Volatility, South Korea, SM. Entertainmnet Co.Ltd, Information, Investation. Type Article : Research Paper